2020
DOI: 10.1002/jbmr.4494
|View full text |Cite
|
Sign up to set email alerts
|

Bone Microarchitecture Phenotypes Identified in Older Adults Are Associated With Different Levels of Osteoporotic Fracture Risk

Abstract: Prevalence of osteoporosis is more than 50% in older adults, yet current clinical methods for diagnosis that rely on areal bone mineral density (aBMD) fail to detect most individuals who have a fragility fracture. Bone fragility can manifest in different forms, and a "onesize-fits-all" approach to diagnosis and management of osteoporosis may not be suitable. High-resolution peripheral quantitative computed tomography (HR-pQCT) provides additive information by capturing information about volumetric density and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…Increasingly, it has been recognized that measurement of BMD alone may not accurately demonstrate bone fragility and predisposition to fracture, and additional approaches to complement BMD measurements in osteoporosis have been reported. ( 34 ) We, therefore, provided a detailed analysis of the biomechanical properties of bone caused by deletion of menin early in the osteoblast lineage. Thus, the mechanical behavior of bone is strongly dependent on its complex organization and hierarchical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, it has been recognized that measurement of BMD alone may not accurately demonstrate bone fragility and predisposition to fracture, and additional approaches to complement BMD measurements in osteoporosis have been reported. ( 34 ) We, therefore, provided a detailed analysis of the biomechanical properties of bone caused by deletion of menin early in the osteoblast lineage. Thus, the mechanical behavior of bone is strongly dependent on its complex organization and hierarchical structure.…”
Section: Discussionmentioning
confidence: 99%
“…The bone phenotypes are based on information captured by standard HR-pQCT measures, which provides extensive information on bone characteristics but is not exhaustive in capturing all attributes that determine bone health, such as the manifestation of void spaces (a new HR-pQCT measure), or tissue-level organization of the extracellular matrix. Although phenotyping may not capture exhaustive information about bone health, the OR analysis reinforced the insight gained with bone phenotyping, revealing that BMD parameters (primarily Tt.BMD and Ct.BMD at the tibia), which were previously identified as imaging biomarkers of fracture for the low density phenotype, (22) were of highest importance in differentiating hip fractures from controls. These findings suggest that the combination of bone characteristics associated with the low density phenotype predispose an individual to higher risk of hip fracture, and thus stratifying the population based on bone phenotypes alongside using phenotype-specific imaging biomarkers could be incorporated into future fracture prediction models to improve patient-specific assessment of fracture risk.…”
Section: Discussionmentioning
confidence: 98%
“…The bone microarchitecture phenotypes of all participants were estimated using a clustering model we recently established with the Bone Microarchitecture International Consortium (BoMIC). (22) Fig. 1.…”
Section: Bone Phenotypingmentioning
confidence: 99%
“…Large case–control and cross-sectional observational studies documented that the micro-architecture of the bone significantly influenced the fracture risk. 85,86 In these studies, it was shown that among osteopenic women those with fragility fractures had a lower trabecular density and a more heterogeneous trabecular distribution compared with non-fractured women with the same BMD. Similarly, HR-pQCT measurements of the cortical parameters of the distal tibia, and in particular its porosity, can distinguish osteopenic women with fractured wrists from non-fractured women.…”
Section: Bone Micro-architecturementioning
confidence: 99%
“…Large case-control and cross-sectional observational studies documented that the micro-architecture of the bone significantly influenced the fracture risk. 85,86 In these studies, it was shown that among osteopenic women those with fragility fractures had a lower trabecular density and a more heterogeneous trabecular distribution compared with non-fractured women with the same BMD.…”
Section: Bone Micro-architecturementioning
confidence: 99%